If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + y = 0 Solving 10x + y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1y' to each side of the equation. 10x + y + -1y = 0 + -1y Combine like terms: y + -1y = 0 10x + 0 = 0 + -1y 10x = 0 + -1y Remove the zero: 10x = -1y Divide each side by '10'. x = -0.1y Simplifying x = -0.1y
| 2.3n+1=1.3n+7 | | 5(b+7)-2=4(b+3)+5 | | 7(x-2)=5(3x+1)+5 | | 6-2x=6x+10 | | 4(s+3)-1=3(2s+1)+5 | | x^2-308x+23716=0 | | 7a-6=19+2a | | 2x=x+26 | | 4r^2-18r-100=0 | | x+(2x)=12xy*y^2 | | -5(t-3)-(t+4)=10 | | A=2(L+W)(W) | | A=2(L+W) | | 21+(-47)+12+38+(-54)= | | 6y-12y+3= | | X^4-5x^3+11x^2-25x+30=0 | | c=gm | | (2x-3y)(x+2y)=0 | | 6y+12y+3= | | X-5=(2x-3) | | 25r^3-9r=0 | | 8x+9=4x-5 | | 4x+5=6x | | 3y+4z=16(y+z) | | 6v^2-3v+1=0 | | X-5=2(3-x) | | (4x-8)-(7x+9)= | | x-4y=u | | 5=4m+4u | | 7x-35+14=7 | | (4/5)1.175= | | 3x-(5x-4)= |